Corporate Taxation and Dividend Behaviour - Feldstein, M. S. (Review of Economic Studies, 1970)
Journal Article Corporate Taxation and Dividend Behaviour Get access M. S. Feldstein M. S. Feldstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 1, January 1970, Pages 57–72, https://doi.org/10.2307/2296498 Published: 01 January 1970 Article history Received: 01 January 1969 Accepted: 01 May 1969 Published: 01 January 1970